An experimental method for simulating core physical property parameters under original conditions

By using real core cuttings to simulate underground conditions in the sand filling pipe, the problem of difficulty in accurately testing core physical properties parameters in the prior art is solved, and high-accurate core physical properties parameter reduction and water-sensitive damage evaluation are achieved.

CN115389388BActive Publication Date: 2025-03-28SHAANXI UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210705909.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-21
Publication Date
2025-03-28
Estimated Expiration
2042-06-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively simulate real underground core conditions, resulting in inaccurate core physical properties parameter test results, and the degree of cementation of artificial cores is difficult to control.

Method used

The independently developed small-volume sand filling pipes with real core cuttings of different particle sizes are used to fill the self-developed small-volume sand filling pipes, combined with a hydraulic press and a homemade filler, and the core physical properties are tested using an automatic tester for measurement of permeability and porosity of nitrogen to simulate the real underground situation.

Benefits of technology

The physical properties parameters of the real underground core were successfully restored, with small errors and reliable experimental results, which can effectively evaluate the water-sensitive damage and shrinkage effect, making it closer to the real underground reservoir environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115389388B_ABST
    Figure CN115389388B_ABST
Patent Text Reader

Abstract

An experimental method for simulating the physical property parameters of cores under original conditions, placing mixed samples with different density requirements into a core simulation device for one-step molding, evaluating water-sensitive damage on the basis of restoring the physical property parameters of the cores under real conditions, comparing the permeability and porosity of the cores before and after damage, calculating the water-sensitive damage rate, and adding a shrinkage and expansion agent for shrinkage and expansion evaluation; the method has the characteristics of cheap and easy-to-buy materials, simple and easy-to-operate preparation methods, and reliable experimental results.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oil and gas field development, and in particular relates to an experimental method for simulating core physical property parameters under original conditions. Background Art

[0002] As an indispensable resource for the economies and people's lives of countries around the world, oil has a huge impact. As a non-renewable resource, oil must be reasonably formulated to further improve the recovery rate of oil fields. The physical parameters of reservoir rocks and fluids are an important basis for reservoir engineering research and oil and gas field development. They are also an important basis for formulating oil field development plans and calculating crude oil reserves.

[0003] At present, there are few cases of using this method for physical simulation at home and abroad. In order to obtain the real physical parameters of fluids under different conditions in rocks, most physical simulation experiments use real cores or artificial cores directly made of sand particles or sand-filled tubes to simulate underground cores. Real underground cores are usually difficult to obtain during the coring process of oil field drilling, so real cores are rarely used for laboratory experiments. Artificial cores are made by cementing different sand particles. They are artificially made to simulate formation conditions. Although they are easy to obtain, the degree of cementation is difficult to control, and they are quite different from the actual conditions of real underground cores. Summary of the invention

[0004] In order to overcome the deficiencies of the above-mentioned prior art, the purpose of the present invention is to provide an experimental method for simulating the parameters of the physical properties of cores under original conditions. The present invention uses real underground core cuttings of different particle sizes to fill into a self-developed recyclable small-volume sand filling tube to restore the original underground conditions. A self-made filler is used and a hydraulic press is used to assist in filling. A nitrogen permeability and porosity automatic tester is used to perform a core physical property test simulation experiment to simulate the physical property parameters of real cores with consistent particle size distribution under different densities under real underground conditions, and is used to evaluate water sensitivity and shrinkage and expansion effects. The authenticity is more scientific and closer to the real underground reservoir environment; it can effectively The invention can restore the underground situation and provide a certain reference for future on-site construction. The sand-filled pipe model of the invention is a device filled with quartz sand. Different permeabilities are controlled by filling quartz sand of different particle sizes and can be recycled. However, since the internal medium filled is quartz sand, the actual situation of the underground real core cannot objectively explain the basic physical properties of the underground rock formation. Moreover, artificial filling affects the compaction of quartz sand, which will cause the porosity and permeability to be particularly large, and ultra-low permeability cannot be obtained. Moreover, the current mechanically pressed sand-filled pipe has a large volume and is inconvenient to operate. The invention has the characteristics of cheap and easy-to-buy materials, simple and easy-to-operate preparation methods, and reliable experimental results.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] An experimental method for simulating the physical property parameters of a core under original conditions, in order to simulate a real core, in the process of preparing an initial sample, a mixed sample with different density requirements is placed in a core simulation device for one-step molding, and water-sensitive damage is evaluated on the basis of restoring the physical property parameters of the core under real conditions, and the permeability and porosity of the core before and after damage are compared, the water-sensitive damage rate is calculated, and a shrinkage and expansion agent is added for shrinkage and expansion evaluation, comprising the following steps:

[0007] Step 1, prepare the gravel filling material mixture: stir evenly, weigh the required amount of the mixture, and keep it for later use;

[0008] Step 2, the bottom of the core sand filling device is first screwed and fixed with a nut without a hole and a round stainless steel filter is embedded; the mixed material prepared in step 1 is added in ten times, and each time it is pressed with a hydraulic press until it is filled to the required position of the mold;

[0009] Step 3: A circular stainless steel filter is embedded in the upper part of the core sand filling device, and the perforated nut is tightened. The solid nut at the lower part of the core sand filling device is removed, and the hollow nut is tightened to obtain the initial sample;

[0010] Step 4, wrap the initial sample prepared in step 3 with plastic wrap, and perform curing for 2 days, and then test the permeability and porosity. After the test, the initial sample is saturated with formation water and then taken out. After wiping off the water, the porosity and permeability of the initial sample are tested, and the water-sensitive damage is calculated;

[0011] Step 5, the initial sample of step 3 is subjected to real repair by shrinkage and expansion agent displacement simulation fluid at a constant temperature of 80°C. After the repair is completed, the water film on the surface of the stainless steel and the hygroscopic top and bottom pore water film are wiped dry, the porosity and permeability are tested again, and the water-sensitive damage repair effect is calculated.

[0012] The gravel filling material mixture comprises: 20 parts of 20-40 mesh gravel rock cuttings; 30 parts of 40-70 mesh gravel rock cuttings; and 50 parts of 70-140 mesh gravel rock cuttings.

[0013] The gravel filling mixture also includes 50 parts of water.

[0014] The gravel filling mixture also includes 10 parts of 1% shrinkage and expansion agent and 20 parts of 2% KCl.

[0015] In the test described in step 4, the initial sample is tested for porosity and permeability data using core porosity and permeability. After the initial sample is tested, it is saturated with formation water and then taken out, the water film on the surface of the stainless steel cylinder is wiped dry, and the water film on the top and bottom pores is absorbed dry, weighed, and the porosity and permeability are measured.

[0016] In the one-step molding method, the required mixed materials are directly added into a stirring container according to the proportion, and the mixed materials are stirred at 50 r / min for 10 minutes to obtain composite rock cuttings and the required mass of the composite rock cuttings at the corresponding density is weighed.

[0017] The curing conditions are as follows: temperature 25°C, humidity 0%, and continuous curing for 2 days.

[0018] An experimental method for simulating the parameters of core physical properties under original conditions, comprising the following steps by weight:

[0019] Step 1, mixing the ingredients in a ratio of 20 parts of 20-40 mesh gravel cuttings, 30 parts of 40-70 mesh gravel cuttings, 50 parts of 70-140 mesh gravel cuttings, and 2 parts, stirring evenly, and the obtained mixed material is set aside;

[0020] Step 2: First, the bottom of the core simulation device is screwed and fixed by a nut without a hole, and a 200-mesh round stainless steel filter is inlaid, and the core sand filling device is inlaid with a round stainless steel filter; the prepared mixed material is added in ten times, and each time it is pressed with a hydraulic press until it is filled to the required position of the mold;

[0021] Step 3: A 200-mesh round stainless steel filter is inlaid on the upper part of the core sand filling device, and the perforated nut is tightened. The solid nut at the lower part of the core sand filling device is removed and the hollow nut is tightened to obtain the initial sample;

[0022] Step 4, wrap the initial sample prepared in step 3 with plastic wrap and cure for 2 days. After the curing is completed, the core physical property test experiment is carried out using nitrogen permeability and porosity automatic testing equipment, and the obtained data is converted into the core physical property parameters under the corresponding volume using the conversion formula.

[0023] The core sand filling device is a hollow tube whose inner cavity can be filled with rock chips of different mesh sizes. Removable nuts are provided at both ends of the tube, and a 200-mesh filter is provided inside the nut to fill the gap and prevent mass loss so as to allow gas and liquid to flow.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] Since the present invention uses rock cuttings instead of quartz sand, the original real core conditions underground can be restored. During the entire experimental process, when the core holder is not depressurized, the core can be perfectly wrapped inside the independently designed sand filling tube, so the core physical property parameter test experiment can be successfully carried out with a small error. After the experiment is completed, analysis is performed based on different density data, and the advantages of the distribution data of the core porosity and permeability at different densities can be clearly seen, which are basically consistent with the physical property parameters of the real area, and can provide new ideas for subsequent related reservoir evaluation experiments. Compared with other domestic and foreign methods that directly use artificial cores or quartz sand filling tubes to test the core physical property parameters, it is more authentic and reliable, and at the same time, it is small in size, can be disassembled and reused, and has certain economic value.

[0026] The present invention uses a self-developed recyclable small-volume sand filling tube for the original underground gravel cuttings, uses a self-made filler and a hydraulic press to assist in filling, inlays customized stainless steel circular filter screens at both ends, and tightens the nut to form. The core physical property test experiment is carried out using a nitrogen permeability and porosity automatic tester. The model has high precision, thereby ensuring that the core holder and the small-volume sand filling tube are seamlessly combined, and the inside of the nut corresponds to a target-shaped diversion channel to ensure excellent dispersion and diversion capabilities. The core physical property test experiment is carried out on the internal simulation core. After the experiment is over, the nut is unscrewed, the internal cuttings are taken out, the model is rinsed, and the next experiment is carried out. The main mechanism of the present invention is to use a self-developed recyclable small-volume sand filling tube to simulate the actual situation of the underground rock formation, and use the different density of the filling cuttings to control different permeabilities and porosities, so as to achieve the maximum restoration of the core physical property parameters under real conditions. The present invention also has the characteristics of cheap and easy-to-buy preparation materials, simple and easy-to-operate preparation methods, and reliable experimental results.

[0027] The present invention studies the influence of formation water on reservoir damage, uses nitrogen permeability porosity automatic tester equipment to conduct core physical property test simulation experiments to simulate the physical property parameters of real cores with inconsistent particle size distribution under different densities under real underground conditions, and can also predict the water-sensitive damage of reservoirs under different densities, and can effectively restore the underground conditions. It is subjected to water-sensitive damage treatment by a vacuum saturation device, and the porosity and permeability are measured again to restore the real reservoir conditions of the target area in a targeted manner and evaluate the corresponding reservoir damage, and then add a laboratory-made shrinkage and expansion agent, and use a core displacement device to repair and evaluate the degree of reservoir damage, and restore the shrinkage and expansion effect in situ. The results show that for the reservoir location in the study area, the content of unstable hydroaluminosilicate minerals such as sand, gravel, mud, tuff and montmorillonite is high, resulting in serious water sensitivity. After prediction through the independently designed experimental scheme, the real core physical properties of the reservoir are targetedly restored and the water-sensitive damage and treatment effect are evaluated. Compared with the real data, the degree of restoration is high. Compared with the single mineral core evaluation experiment, the experimental method is more scientific. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a structural schematic diagram of the sand-filled tube model.

[0029] Figure 2(a) is a graph showing the test permeability results.

[0030] Figure 2(b) is the test porosity result diagram.

[0031] Figure 2(c) is a correlation diagram between the test porosity and permeability.

[0032] Figure 2(d) is a correlation diagram between the test porosity and permeability.

[0033] Figure 3(a) is a permeability test diagram of the water-sensitive damage evaluation and treatment and restoration effect evaluation experiment.

[0034] Figure 3 (b) is a porosity test diagram of the water-sensitive damage evaluation and treatment and restoration effect evaluation experiment.

[0035] Figure 4 This is a diagram of the experimental setup for evaluating water-sensitive damage and the effectiveness of treatment and restoration.

[0036] Figure 5(a) is a water-sensitive injury diagram.

[0037] Figure 5(b) is a diagram of the water-sensitive injury mechanism.

[0038] Figure 5 (c) is a diagram of the shrinkage-expansion effect mechanism.

[0039] In the figure: 1-water bucket; 2-constant flow pump; 3-six-way valve 1; 4-swelling agent container; 5-sand carrying liquid container; 6-piston; 7-core clamp; 8-confining pressure applicator 1; 9-axial pressure applicator; 10-six-way valve 2; 11-confining pressure applicator 2. DETAILED DESCRIPTION

[0040] The present invention will be further described below in conjunction with specific implementation modes.

[0041] An experimental method for simulating core physical property parameters under original conditions, comprising the following steps: filling a reusable core sand filling tube device (also called sand filling tube) with gravel cuttings, inlaying 200-mesh stainless steel circular filter screens at both ends of the sand filling tube, tightening nuts at both ends of the sand filling tube, forming in one step, and conducting core physical property test experiments, water-sensitive damage evaluation, and shrinkage and expansion effect evaluation experiments.

[0042] The main contents of the present invention are the required materials, formula and operation method, and the quality formula is as follows:

[0043] Table 1 Formulation of underground real core filling materials

[0044]

[0045] Table 2 Formulation of rock cuttings combination materials for core physical property simulation experiment

[0046]

[0047] The composite conglomerate core filler used in the present invention is: conglomerate filler with an average particle size of 0.5 mm, with a mass ratio of 20%, conglomerate filler with an average particle size of 0.8 mm, with a mass ratio of 30%, and conglomerate filler with an average particle size of 1.5 mm, with a mass ratio of 50%. The core fragments are provided by a domestic oil field, and the internal gravel particles are removed after being knocked open for processing and grinding;

[0048] The operation method adopted by the present invention is as follows: adding the required composite mixed material into a JSF-550 type agitator (other brands of agitators are also acceptable) according to the formula ratio, with a rotation speed of 50 r / min and a duration of 10 minutes. After being evenly stirred, the mixed material is put into a mold and stirred evenly. The mass of the required mixed material corresponding to the block reservoir density is calculated and kept for later use. The bottom of the core simulation device is first screwed and fixed by a nut without holes and inlaid with a circular stainless steel filter. Next, the prepared mixed material is added in ten times, and the same number of times is pressed by a hydraulic press each time until the required position of the mold is filled. The upper part is inlaid with a circular stainless steel filter, and the nut with holes is tightened to make the nut and the core precisely combined. The solid nut is removed from the lower part, and the hollow nut is tightened. The sample is wrapped with a plastic wrap for 2 days of curing. After the curing is completed, a core physical property test experiment is carried out using a nitrogen permeability and porosity automatic test device, and the obtained data is converted into core physical property parameters under the corresponding volume using a conversion formula. Example

[0049] Prepare the ingredients according to the formula ratio in Table 2 and stir evenly. Calculate the required mass of the first group at different densities and keep them for later use. Screw and fix the bottom of the core sand filling tube device with a nut without holes and inlay a round stainless steel filter. Then add the prepared mixed material in ten times and press it with a hydraulic press each time until it is filled to the required position of the mold. Inlay a round stainless steel filter on the top and tighten the nut with holes. Remove the solid nut from the bottom and tighten the hollow nut. Wrap the sample with plastic wrap for 2 days of curing, and test its permeability and porosity. See Figure 2, Figure 2(a) is the test permeability result; Figure 2(b) is the test porosity result; Figure 2(c) is the test correlation between porosity and permeability; Figure 2(d) is the test correlation between porosity and permeability. From the real data of the region, near the density of 2.1, the porosity and permeability of the real formation can be restored, distributed in the permeability of 1MD and the porosity of about 20%, and the permeability and porosity data under the real density of the reservoir are taken, as shown in Figure 2(d). By comparing the test with the actual value, it is found that the test results are true and reliable, which can effectively restore the reservoir physical properties in different regions, laying a good foundation for the next evaluation experiment. Example

[0050] Mix the ingredients according to the formula ratio in Table 2, stir evenly, calculate the mass required for the second group under different densities, and keep it for later use. The bottom of the independently developed small-volume core sand filling tube device is first screwed and fixed by a nut without holes and inlaid with a round stainless steel filter. Then, the prepared mixed material is added ten times, and each time it is pressed with a hydraulic press until it is filled to the required position of the mold. The upper part is inlaid with a round stainless steel filter, the nut with holes is tightened, the solid nut is removed from the lower part, and the hollow nut is tightened. The sample is wrapped with plastic wrap for 2 days of maintenance. After the measurement, the sample is saturated with water using a vacuum saturation device to simulate water-sensitive damage. After the treatment, the porosity and permeability are measured. See Figure 3. Figure 3 (a) is a water-sensitive damage evaluation diagram. The results show that the water-sensitive damage in this area is serious, reaching 45%. It can be seen that as the density of the reservoir increases, the water-sensitive damage permeability and porosity decrease under different density conditions, and at the most serious damage of 2.2g / cm 3 It shows that the reservoir damage is the most serious, indicating that this method can effectively simulate the real water-sensitive damage in the underground. Example

[0051] Mix the ingredients according to the formula ratio in Table 2 and stir evenly. Calculate the required mass of the third group at different densities and keep them for later use. The bottom of the independently developed small-volume core sand filling tube device is first screwed and fixed by a nut without holes and inlaid with a round stainless steel filter. Then, the prepared mixed material is added in ten times and pressed with a hydraulic press each time until it is filled to the required position of the mold. A round stainless steel filter is inlaid on the upper part, and the nut with holes is tightened. The solid nut is removed from the lower part and the hollow nut is tightened. The sample is wrapped with plastic wrap for 2 days of maintenance. After the measurement, the sample is treated with water-sensitive damage using a vacuum saturation device. After the treatment, the porosity and permeability are measured. The water-sensitive sample is then displaced by a shrinkage and swelling agent system to simulate the real repair process of the fluid, and the process is carried out at a constant temperature of 80°C. After the end, the water film on the stainless steel surface and the hygroscopic top and bottom pore water film are wiped dry, and the porosity and permeability are measured. See Figure 3. Figure 3(a) is a permeability test diagram of the water-sensitive damage evaluation and treatment and repair effect evaluation experiment; Figure 3(b) is a porosity test diagram of the water-sensitive damage evaluation and treatment and repair effect evaluation experiment. The test results show that after adding real cores and filling them in the independently designed sand filling tubes, the water-sensitive damage can be effectively evaluated, and after adding the shrinkage and swelling agent system, the reservoir damage in the area can be effectively repaired. The reservoir damage repair effect in different density areas is obvious. The repair rates of different density areas are 35%, 32%, 28%, 37% and 26% respectively according to the density. Most of the reservoir damage in this area is about 45%. However, after simulation with this method, the reservoir repair state can be obviously restored. According to the experimental mechanism, this method uses different proportions of rock minerals to match the mineral composition, and the reduction degree is improved, which further illustrates the reliability of the scheme.

[0052] The core test, water sensitivity and damage degree repair measurement method adopted by the present invention is: the permeability of the sample after the water sensitivity damage repair experiment is converted to obtain the change in the damage degree. The calculation formula involved is as follows:

[0053] 1) The core permeability formula is calculated as follows:

[0054] (1)

[0055] Where:

[0056] K——core permeability, mD;

[0057] Q——Flow rate of fluid flowing through rock per unit time, cm 3 / s;

[0058] µ——Viscosity of the fluid, Pa˙s;

[0059] L – length of the rock, cm;

[0060] A——cross-sectional area of ​​fluid flowing through rock, cm 2 ;

[0061] ΔP – pressure difference before and after the fluid passes through the rock, MPa.

[0062] 2) The core porosity formula is calculated as follows:

[0063] (2)

[0064] Where:

[0065] ɸ——porosity, %;

[0066] Vp – pore volume of the core;

[0067] Vr - the external volume of the core.

[0068] 3) The core damage rate formula is calculated as shown below:

[0069] (3)

[0070] Where:

[0071] K d ——core damage rate, %;

[0072] K 1 ——Brine permeability, ×10 -3 µm 2 ;

[0073] K 2 ——Permeability of the fluid, ×10-3 µm 2 .

[0074] The physical parameters of the cores of all samples under different conditions were calculated, and the degree of reduction was compared with the cores under the actual density. The reservoir damage and water sensitivity control degree under different densities were evaluated. The three evaluation methods were used to evaluate the cores under different densities. It can be seen that the designed experimental method has a high degree of core physical property reduction, and can be used to evaluate the real physical properties of sandy conglomerate reservoirs and reservoir damage experiments such as water sensitivity and physical parameters after water sensitivity repair, with strong reliability; and sandy conglomerate reservoirs have rapid accumulation near the source, mixed sand, gravel and mud, and high content of unstable hydroaluminosilicate minerals such as tuff and montmorillonite, and are generally severely water-sensitive. A shrinking and swelling agent system can be added to modify the clay lattice through physical and chemical reactions with clay minerals so that it does not expand when it meets water; the expanded clay lattice releases water molecules after being modified by chemical reactions, and the lattice shrinks. And through multi-point adsorption, these modified clay materials are firmly combined with the original formation minerals, thus avoiding the damage to the formation caused by the expansion and migration of clay minerals in contact with water. After the shrinkage and swelling agent is added, the cations with oxidizing groups replace the cations with hydration membranes in montmorillonite. The oxidizing groups can precipitate water between crystal layers, reduce the distance between montmorillonite layers, shrink the volume, and have obvious shrinkage and swelling effects. However, the current shrinkage and swelling effects and water-sensitive treatment effect evaluation methods are single. This method is urgently needed to truly restore the underground reservoir conditions, and compared with real cores that are difficult to obtain, this method can simulate real ore types to restore physical property parameters, and evaluate reservoir water-sensitive damage and water-sensitive damage treatment effects, which can be used to evaluate core damage experiments later.

[0075] The present invention studies the mechanism, and the results show that the addition of shrinkage and swelling agent has a better effect on the repair of water-sensitive damage to the reservoir, the restoration of core physical property parameters is highly realistic, and the data obtained is closer to the real formation. The performance test method adopted by the present invention is: the cured samples are subjected to core physical property test simulation experiments using nitrogen permeability and porosity automatic tester equipment to simulate and restore the actual underground situation, and the core damage and treatment evaluation experiments are carried out using vacuum saturation pressurization devices and displacement devices.

[0076] See also Figure 1 , Figure 1 (a) is the structural schematic diagram of the sand-filled tube model. Figure 1 is a schematic diagram of a sand filling tube model, wherein the core sand filling device (also called sand filling tube) is a hollow tube with a built-in hollow core that can be filled with rock cuttings of different mesh sizes, and can be disassembled with nuts at both ends, see Figure 1and fill the gaps with 200-mesh filter gaskets; Part A is the filler of the core sand filling device, and Part B is the overall structure of the core sand filling device, with threads at both ends; Parts C and D are the nuts of the core sand filling device, with air intake columns at both ends and target threads at the bottom to increase the flow conduction capacity.

[0077] See Figure 2, Figure 2(a) is the test permeability result; Figure 2(b) is the test porosity result; Figure 2(c) is the test correlation between porosity and permeability; Figure 2(d) is the test correlation between porosity and permeability. From the real data of the region, near the density of 2.1, the porosity and permeability of the real formation can be restored, distributed in the permeability of 1MD and the porosity of about 20%, and the permeability and porosity data under the real density of the reservoir are taken, as shown in Figure 2(d). By comparing the test with the actual value, it is found that the test results are true and reliable, which can effectively restore the reservoir physical properties in different regions, laying a good foundation for the next evaluation experiment.

[0078] See Figure 3. Figure 3(a) is a permeability test diagram of the water-sensitive damage evaluation and treatment and repair effect evaluation experiment; Figure 3(b) is a porosity test diagram of the water-sensitive damage evaluation and treatment and repair effect evaluation experiment. The test results show that after adding real cores and filling them in the independently designed sand filling pipes, the water-sensitive damage can be effectively evaluated, and after adding the independently designed shrinking and swelling agent system, the reservoir damage in the area can be effectively repaired, with obvious significant results reaching 37%.

[0079] See also Figure 4 , Figure 4 This is a diagram of the experimental device for evaluating water-sensitive damage and evaluating the effect of treatment and restoration; a water bucket 1 is connected to a six-way valve 3 through a constant flow pump 2; the six-way valve 3 is also connected to the outlets of a confining pressure applicator 8, a shrinkage and expansion agent container 4, and a sand-carrying liquid container 5 respectively; the outlets of the shrinkage and expansion agent container 4 and the sand-carrying liquid container 5 are connected to the inlet of a core holder 7 through another six-way valve 10; the outlet of the core holder 7 is connected to the inlet of a confining pressure applicator 11 and an axial pressure applicator 9 respectively with a connecting pipe; the working sequence of the experimental equipment is to use a multifunctional displacement system as the experimental equipment, perform Brazilian splitting on the core after oil washing, apply a confining pressure of 25 MPa, first use water as the displacement fluid to carry out a displacement experiment and record the displacement pressure change, and calculate the initial permeability K of the core after the liquid discharge rate at the tail of the core holder is stable. 1 The above experiment was repeated after the shrinkage and expansion system was evenly dispersed in the fracturing fluid system. The permeability K of the repaired core was 2 The core injected with the diverting fracturing material was placed in the core saturation system and pressurized at 40MPa and 90℃ for 12h to simulate the high temperature and high pressure environment in the formation, and then the core was taken out. Permeability K 2 With the initial permeability K 1 The ratio is the core permeability recovery value.

[0080] See Figure 5. Figure 5 (a) is a water-sensitive damage diagram: Since the hydration expansion of the reservoir is mainly caused by the clay minerals contained in the reservoir, the hydration expansion of the clay minerals with water is mainly due to the lack of hydrogen bonds between the silicon-oxygen tetrahedron and the aluminum-hydrogen-oxygen octahedron units in montmorillonite, and the mutual connection is weak. The polar Si-O and O-H bonds on the surface of the crystal layer can adsorb water molecules of the same polarity, and the water molecules can enter between the two crystal layers of the clay mineral, increasing the interlayer distance, resulting in hydration expansion and decreased permeability. The water molecules adsorbed on the surface of the crystal layer can form a hydration film on the surface of the clay mineral, expanding the distance between the clay lattice layers, and causing the clay to swell and disperse; Figures 5 (b)-(c) are shrinkage and expansion effect mechanism diagrams: the cations with hydration films in montmorillonite are replaced by cations with oxidizing groups, and their oxidizing groups can cause water between the crystal layers to precipitate, reducing the interlayer distance of montmorillonite and shrinking the volume.

Claims

1. An experimental method for simulating the parameters of core physical properties under original conditions, characterized by: In order to simulate the real core, the mixed samples with different density requirements are placed in the core simulation device for one-step molding. The water-sensitive damage is evaluated on the basis of restoring the core physical parameters under real conditions. The permeability and porosity of the core before and after damage are compared, the water-sensitive damage rate is calculated, and the shrinkage and expansion agent is added for shrinkage and expansion evaluation, including the following steps: Step 1: Prepare the gravel filling material mixture according to the formula: stir evenly, calculate the amount of the required mixture, and keep it for later use; Step 2, the bottom of the core sand filling device is first screwed and fixed with a nut without a hole and a round stainless steel filter is embedded; the mixed material prepared in step 1 is added in ten times, and each time it is pressed with a hydraulic press until it is filled to the required position of the mold; Step 3: A circular stainless steel filter is embedded in the upper part of the core sand filling device, and the perforated nut is tightened. The solid nut at the lower part of the core sand filling device is removed, and the hollow nut is tightened to obtain the initial sample; Step 4, wrap the initial sample prepared in step 3 with plastic wrap, and perform curing for 2 days, and then test the permeability and porosity. After the test, the initial sample is saturated with formation water and then taken out. After wiping off the water, the porosity and permeability of the initial sample are tested, and the water-sensitive damage is calculated; Step 5, the initial sample of step 3 is subjected to real repair by shrinkage and expansion agent displacement simulation fluid at a constant temperature of 80°C. After the repair is completed, the water film on the surface of the stainless steel and the hygroscopic top and bottom pore water film are wiped dry, the porosity and permeability are tested again, and the water-sensitive damage repair effect is calculated.

2. The experimental method for simulating the parameters of core physical properties under original conditions according to claim 1, characterized in that: The gravel filling material mixture comprises: 20 parts of 20-40 mesh gravel rock cuttings; 30 parts of 40-70 mesh gravel rock cuttings; and 50 parts of 70-140 mesh gravel rock cuttings.

3. The experimental method for simulating the parameters of core physical properties under original conditions according to claim 2, characterized in that: The gravel filling mixture also includes 50 parts of water.

4. The experimental method for simulating the parameters of core physical properties under original conditions according to claim 3, characterized in that: The gravel filling mixture also includes 10 parts of 1% shrinkage and expansion agent and 20 parts of 2% KCl.

5. The experimental method for simulating core physical property parameters under original conditions according to claim 1, characterized in that: In the test described in step 4, the initial sample is tested for porosity and permeability data using core porosity and permeability. After the initial sample is tested, it is saturated with formation water and then taken out, the water film on the surface of the stainless steel cylinder is wiped dry, and the water film on the top and bottom pores is absorbed dry, weighed, and the porosity and permeability are measured.

6. The experimental method for simulating core physical property parameters under original conditions according to claim 1, characterized in that: In the one-step forming, the required mixed materials are directly added into a stirring container according to the proportion, and the mixed materials are stirred at 50 r / min for 10 minutes to obtain composite rock cuttings and the required mass of the composite rock cuttings at the corresponding density is weighed.

7. The experimental method for simulating core physical property parameters under original conditions according to claim 1, characterized in that: The curing conditions are as follows: temperature 25°C, humidity 0%, and continuous curing for 2 days.

8. An experimental method for simulating the parameters of core physical properties under original conditions, characterized by: The following steps are involved: Step 1, mixing the ingredients in a ratio of 20 parts of 20-40 mesh gravel cuttings, 30 parts of 40-70 mesh gravel cuttings, 50 parts of 70-140 mesh gravel cuttings, and 2 parts, stirring evenly, and the obtained mixed material is set aside; Step 2: First, the bottom of the core simulation device is screwed and fixed by a nut without a hole, and a 200-mesh round stainless steel filter is inlaid, and the core sand filling device is inlaid with a round stainless steel filter; the prepared mixed material is added in ten times, and each time it is pressed with a hydraulic press until it is filled to the required position of the mold; Step 3, inlay a 200-mesh round stainless steel filter screen on the upper part of the core sand filling device, tighten the perforated nut, remove the solid nut on the lower part of the core sand filling device, and tighten the hollow nut to obtain the initial sample; Step 4, wrap the initial sample prepared in step 3 with plastic wrap and cure for 2 days. After the curing is completed, the core physical property test experiment is carried out using nitrogen permeability and porosity automatic testing equipment, and the obtained data is converted into the core physical property parameters under the corresponding volume using the conversion formula.

9. The experimental method for simulating core physical property parameters under original conditions according to claim 8, characterized in that: The core sand filling device is a hollow tube whose inner cavity can be filled with rock cuttings of different mesh sizes, and a 200-mesh filter is arranged on the inner side of the nut.

Citation Information

Patent Citations

  • High-seepage stripe rock core model, and manufacturing method and device thereof

    CN106324223A

  • Laboratory measurement of dynamic fracture porosity and permeability variations in rock core plug samples

    US20210010922A1